El Centro de Habilidades Clínicas: una respuesta a los cambios - Kunakov, Natasha; Bozzo N., Sergio (Revista Hospital Clínico Universidad de Chile, 2014)
Medical education is now living a new scenario. No longer can we teach our students with as many real patients as we used to do. The use of new teaching resources has become mandatory. Our Faculty of Medicine has built a Simulation Centre, located in Campus Occidente especially designed to teach clinical habilities. This articles tells us what this Center can offer us